Bean production areas in sub-Saharan Africa - Farrow, A.; Muthoni Andriatsitohaina, Rachel; Ongom, B.; Ojara, M. (Pan-Africa Bean Research Alliance, 2020)
176 bean production areas were identified and reviewed using a form of the Delphi method of consensus building among experts from almost all bean producing countries of sub-Saharan Africa. Data were collected for: bean production, cropping systems and producers; seed systems; bean use and marketing; bean grain types and varieties; and abiotic and biotic constraints to bean production and storage. Data on harvested area and production were compiled from a variety of sources and allocated among bean production areas using local expert knowledge and/or sub-national statistics. Bean environments were computed and allocated to each bean production area. The dataset includes raw data from each workshop; for some variables the data were later standardised to ensure that the cumulative values were 100%. We recommend using the standardised data. (2019-11-27)